Clinical and pathological analyses of two cases of inflammatory bowel disease with cutaneous manifestations - QIU Xiaoying; XIA Chuangang; XIAO Wen; CHEN Fangru (Pifu-xingbing zhenliaoxue zazhi)
Objective To analyze the clinical and histopathological features of skin manifestations of inflammatory bowel disease (IBD) in order to provide guidance for clinical diagnosis. Methods Clinical and pathological characteristics of 2 patients with IBD were retrospectively analyzed. Results One patient had Crohn's disease manifested by perianal erythema and ulcers, and histopathology showed non-caseous and non-infectious granuloma in the dermis. Treatment with Ustekinumab decreased the ulcerative area. In another case of ulcerative colitis with extraintestinal manifestations, erythemas and nodules were all over the body, and ulcers were on the lower legs and buttocks. Histopathology showed dermal neutrophil infiltration. The skin lesions partially subsided after the treatment with Infliximab. Conclusions IBD with cutaneous manifestations has different histopathological characteristics, and clinicians should make the diagnosis based on both clinical manifestations and histopathological features in order to avoid misdiagnosis and missed diagnosis.